Independence of Santri: Exploring the Teachings of the Quran for the Awakening of the Spirit - Yunus, Badruzzaman M.; Syu’aib, Ibrahim; Ahmad, Khadher (FISIP UIN SGD Bandung, 2024)
This study examines the role of religious education in shaping students' independence and character development, particularly within Islamic boarding schools (pesantren). Religion plays a fundamental role in instilling moral values and guiding behavior, and in the pesantren environment, religious practices such as communal prayers, Qur’an recitation, and adherence to Islamic rituals foster noble character traits among students. Islamic education in pesantren not only deepens students' religious knowledge but also encourages the application of Islamic teachings in daily life, promoting personal growth and social responsibility. This study uses the Service Learning (SL) approach, combining academic learning with real-world community engagement. SL projects were conducted within pesantren settings, allowing students to practice autonomy and responsibility through community-centered projects that reflect Islamic values of self-reliance and compassion. Results indicate that students demonstrate a significant understanding of independence, relating it to Islamic principles such as self-sufficiency, resilience, and trust in God after putting forth effort. Findings suggest that students internalize the concept of independence not only as the ability to manage their own needs but also as a commitment to positively impacting their surroundings. The SL approach strengthens this sense of responsibility, bridging theoretical lessons with practical applications that enhance social skills, critical thinking, and self-discipline. The study concludes that pesantren education, enriched with SL-based activities, effectively nurtures independent, socially responsible individuals prepared to face contemporary challenges. Contribution: This research contributes to the discourse on educational methodologies in religious contexts, providing a framework for enhancing character education through experiential learning that aligns with Islamic principles.